The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s12291-009-0068-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin C and E activity on surgically removed cataractous human lens epithelium cells

Abstract: Oxidative stress has been proposed as a common underlying mechanism of cataractogenesis. Experimental and observational data suggest that micronutrients like vitamin C and vitamin E with antioxidant capabilities may retard the development of age-related cataract. Effect of these factors on lens epithelium cells, center of lens metabolic activities, is not completely elucidated. The aim of present study was to examine the effect of vitamin C and E on surgically removed lens epithelium cells of patients with cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…While vitamin C has been noted as a vital antioxidant in the vitreous humor, it was shown to be toxic to lens and retinal epithelial cells and cause lens protein crosslinking at physiological concentrations (1-2 mM) in vitro. 3,26,[52][53][54][55] Vitamin C also degrades rapidly in solution, limiting its long-term effectiveness. We proposed to use glutathione in conjunction with vitamin C to prolong the antioxidant activity of vitamin C and curtail its cytotoxicity at high concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While vitamin C has been noted as a vital antioxidant in the vitreous humor, it was shown to be toxic to lens and retinal epithelial cells and cause lens protein crosslinking at physiological concentrations (1-2 mM) in vitro. 3,26,[52][53][54][55] Vitamin C also degrades rapidly in solution, limiting its long-term effectiveness. We proposed to use glutathione in conjunction with vitamin C to prolong the antioxidant activity of vitamin C and curtail its cytotoxicity at high concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies corroborate the presented data and showed that 0.1 mM was the optimal concentration at preventing oxidative damage. 54,55 Since the reported concentration of vitamin C in the vitreous is between 1 and 2 mM, there must be an explanation for this discrepancy. The hydrogel vitreous substitute did not provide significant reduction to the ROS activity of lens cells compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…PEGDA‐ co ‐PEGMA hydrogel loaded with vitamin C resulted in the lowest ROS activity, followed by PEGDA hydrogel loaded with vitamin C, and vitamin C alone. Vitamin C is an antioxidant and has been shown to protect cells from ROS . Cells treated with vitamin C showed reduced ROS activity, as anticipated.…”
Section: Discussionmentioning
confidence: 99%